The influence of the banking sector on the security of financial market - Борисюк, Олена Володимирівна; Стащук, Олена Володимирівна; Рудик, Наталія Іванівна; Borysiuk, Olena V.; Stashchuk, Olena V.; Rudyk, Natalia I. (ISMA University Riga, 2019)
A dominant role in the financial market of Ukraine are plays the banking system. Improper performance of the banking system by its core functions undermines economic ties between business entities and becomes one of the main threats to the financial market of Ukraine. In general, according to scientists, the economic security of the country is a separate element of the system financial security of the country, which ensures the state of protection of the vital important needs and interests of person, country and society in the economic sphere from internal and external challenges, threats and dangers [5]. In general sense the financial-economic security of the banking system is the state of most effective use of financial resources to prevent threats and ensure the stable functioning of banking activities. The main objective of ensuring the economic security of the banking system is to achieve maximum stability of its functioning, as well as to create the bases and prospects of its development regardless from objective and subjective factors and threats.
Розвиток фінансового ринку як фактор економічної безпеки України
Keywords: фінансовий ринок; безпека; загрози банківського сектора; комерційні банки